Analisis Linguistik Diakronis Bahasa Ogan dan Bahasa Mentawai pada Tataran Fonologi dan Leksikal: Indonesia - Rahmad Kurniawan; Fadiil Reza Mombai; Cesario Galang Rosalianto; Dimas Aprilliansyah; Gigan Satria Lanangku; Yunus Sulistyono (Universitas Muhammadiyah Surakarta, 2026)
This research examines the diachronic linguistic relationship between Ogan and Mentawai, two Austronesian languages in Sumatera, at the phonological and lexical levels. Using comparative-historical methods with Swadesh basic vocabulary words, this study aims to reveal sound correspondence patterns and genetic relationships between the two Austronesian languages. Data were collected through reading and note-taking techniques, then analyzed using lexicostatistical methodsand phonemic correspondence analysis. The results show 20 cognate words with a kinship percentage of 18.18%, placing them in the Families of Stock category according to Crowley’s classification. Phonological analysis reveals systematic sound correspondences at word-final positions: /i/ in Ogancorresponds to /ei/ in Mentawai (ati atei ‘hati’, mati matei ‘mati’), and /ə/ in Ogan corresponds to /a/ in Mentawai (duə dua ‘dua’, matə mata ‘mata’). Despite originating from the same proto-language, geographical separation and regional isolation have caused significant lexical divergence. This research contributes to the documentation and preservation of regional languages in the Indonesian archipelago and enriches understanding of Austronesian language development inIndonesia.